Sosialisasi PHBS dan Cara Melakukan CTPS Kepada Siswa/I di SD 7 Nisam Aceh Utara - Dian Rahayu; Gelva Irayana; Kiki Asrifa Dinen; Ully Fitria (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
Clean and Healthy Living Behavior (PHBS) is one of the preventive efforts in maintaining individual health, with washing hands with soap (CTPS) as one of its main aspects. Elementary school children are among the groups that are vulnerable to disease due to lack of awareness of cleanliness, so socialization is needed to increase their understanding of the importance of CTPS. This study aims to socialize PHBS and how to do CTPS to students of SD 7 Nisam, North Aceh, through interactive educational methods. The activities were carried out by presenting material using PowerPoint, interactive discussions, direct practice of the six steps of CTPS according to WHO standards, and evaluation through questionnaires before and after the activity. The results of the activity showed that the method applied succeeded in increasing students' understanding of the importance of washing hands with soap. Students were more enthusiastic in participating in activities when given an interesting approach that was appropriate for their age. In addition, the involvement of teachers and schools in providing supporting facilities contributed to the success of this program. With this socialization, it is hoped that students can apply the habit of washing their hands independently and consistently, both at school and at home, so that it can reduce the incidence of infectious diseases related to hand hygiene.